Evaluation of the Production Process of the Cover Plate Components Using Time Study Technique - Jamaludin, Mohd Hazrein; Ahmad, Aida Husna; Osman, Saliza Azlina; Osman, Shahrul Azmir (International Journal of Integrated Engineering, 2024)
Time study plays a crucial role in optimizing production efficiency and resource utilization in manufacturing processes. Time study helps to counter problems that occur in the production industry such as uneven task distribution, bottlenecks, idle time, complexity, and time constraints. In this case study, Intec Precision Engineering Sdn Bhd has offered to conduct the time study for packing department that produced cover plate component in order to identify the task time, normal time and standard time. There are 12 work elements that were identified in this case study and these work elements were grouped into 5 different workstations based on cycle time. As a result, among of 12 work elements, the first 7 work elements indicates that the processes did not show any delay, where the processes can be done in range of 12% to 31% faster than the expected standard time. Meanwhile the other 5 work elements indicates a delay in task completion, which is up to 184.7 sec. In case of workstation analysis, workstation 1, 2 and 3 showcasing effective performance in terms of task completion, with 14.6% to 31.1% faster than the standard time. However, for workstation 4 and 5 were recorded a procrastinate process time about 8% and 40%, which can translated as 30.2 sec and 249.4 sec, respectively. As a conclusion, the task time, normal time, and standard time for each of the work elements are identified and proposed to the company as preliminary standard time. This is important for the company to take the work study improvement issue into consideration, where this moderate production may affected the overall production line that can cause harm to the company’s reputation, qualities and expenditures.